PENYIMPANGAN UNSUR KEAMBIGUAN DALAM TEKA-TEKI SUNDA - Hera Meganova Lyra (ETNOLINGUAL, 2018)
This research describes the deviation of ambiguity element in Sundanese riddles. The research focuses on the linguistic matter regarding the deviation, characteristics, and functions of riddles in Sundanese society. The method used was descriptive method by using riddles structure theory of Young Ho (2002) and Ullmann (2012) and the folklore theory by Tarigan (1980). Through the theory of riddle structure, it is concluded that the deviation of ambiguity element in Sundanese riddles occurs in the levels of Phonology, Morphology, Syntax, and Semantics. From the folklore theory, it is determined that the characteristic of riddles in Sundanese society is the comparison of entertainment with the function of practicing cleverness.